Prevention and Treatment of Intestinal Failure–Associated Liver Disease in Children - Raphael, Bram P.; Duggan, Christopher (Seminars in Liver Disease, 2012)
Intestinal failure–associated liver disease (IFALD), a serious complication occurring in infants, children, and adults exposed to long-term parenteral nutrition (PN), causes a wide-spectrum of disease, ranging from cholestasis and steatosis to fibrosis and eventually cirrhosis. Known host risk factors for IFALD include low birth weight, prematurity, short bowel syndrome, and recurrent sepsis. The literature suggests that components of PN may also play a part of the multifactorial pathophysiology. Because some intravenous lipid emulsions (ILEs) may contribute to inflammation and interfere with bile excretion, treatment with ILE minimization and/or ILEs composed primarily of omega-3 fatty acids can be helpful, but requires careful monitoring for growth failure and essential fatty acid deficiency (EFAD). Data from randomized controlled trials are awaited to support widespread use of these approaches. Other IFALD treatments include cycling PN, ursodeoxycholic acid, sepsis prevention, photoprotection, and polyvinylchloride-free tubing. Management and prevention of IFALD remains a clinical challenge.
Keywords: intestinal failure–associated liver disease; parenteral nutrition associated cholestasis; parenteral nutrition; short bowel syndrome; intravenous lipid emulsions